Development of a quantitative immuno-affinity test column assay for on-site screening of clindamycin residues in milk. (April 2016) - Wang, Xiaomei; Luo, Pengjie; Chen, Jinlian; Huang, Yuting; Jiang, Wenxiao
Abstract: A sensitive and specific monoclonal antibody against clindamycin (CLIN) was produced and used to develop an immuno-affinity test column (IATC) assay for on-site screening of CLIN residues in milk. The qualitative limit of detection of the IATC assay, estimated as 1.0 μg L −1  by visual detection, was sufficient to measure maximum residue levels for lincosamide antibiotics in milk. The quantitative IATC assay resulted in a lower detection limit (0.11 μg L −1 ) by evaluating the colour intensity of the test layers, which was approximately 9 times greater sensitivity than visual detection. During the spike and recovery test, the average recoveries ranged from 76% to 114% at different spiked levels, and the intra-/interday coefficients of variation were in the range 9.6–16.7%. The detection time was shortened to 20 min, whereas the sensitivity was comparable with a traditional ELISA. The IATC assay shows promise for on-site screening of CLIN residues in milk.